Crosstalk Between Acid Sphingomyelinase and Inflammasome Signaling and Their Emerging Roles in Tissue Injury and Fibrosis - Li, Cao; Guo, Shanshan; Pang, Wenyuan; Zhao, Zhigang (Frontiers in Cell and Developmental Biology, 2020)
Inflammasomes are a group of protein complexes that are assembled by pattern recognition receptors following the recognition of invading pathogens or host-derived danger signals. Inflammasomes such as NLRP3 mediate the activation of caspase-1 and the production of the proinflammatory cytokines IL-18 and IL-1β. Regulation of inflammasome signaling is critical for host defense against infections and maintenance of cellular homeostasis upon exposure to multiple harmful stimuli. Recent studies have highlighted an important role of acid sphingomyelinase in regulating inflammasome activation. Acid sphingomyelinase hydrolyzes sphingomyelin to ceramide, which further fuses to large ceramide-enriched platforms functioning in stabilizing and amplifying molecules and receptors. Here, we will discuss the current understanding of the acid sphingomyelinase-ceramide system in inflammasome activation, and how it contributes to multiple diseases. Insights into such mechanisms would pave the way for further exploration of novel diagnostic, preventative, and therapeutic targets against tissue injury and fibrosis